Tourism Immiserization: Fact or Fiction? - Nishaal Gooroochurn; Adam Blake (Fondazione Eni Enrico Mattei (FEEM), 2005)
Tourism plays a major part in the development strategies of both developing and developed countries because of the alleged potential of generating foreign exchange, economic growth and welfare enhancement (Sinclair and Stabler, 1997; Sinclair, 1988). Consequently, in several countries a considerable amount of resources is allocated to further promote the tourism sector in a hope of reaping more economic benefits. However, it is still debatable whether tourism is beneficial for the tourist-receiving country or not. While empirical studies (Adams and Parmenter, 1994; Zhou et al., 1996, Baaijens et al., 1998; Blake, 2000; Blake et. al., 2003; Dwyer et al., 2003), argue that tourism expansion is beneficial to the economy, theoretical studies (Copeland, 1991; Chen and Devereux, 1999; Hazari and Nowak, 2003; Hazari et al., 2003; Nowak et al., 2003) posit that tourism expansion can be immiserizing. This paper critically reviews the theoretical and empirical literature to identify the sources via which tourism expansion can benefit or harm the economy. The issues are then empirically investigated using a CGE model for Mauritius to identify the conditions under which tourism expansion can be immiserizing.
Keywords: L83; Q26; 330; Tourism; Immiserization; Welfare; Economic growth